Faktor Penentu Perilaku Hijau untuk Mengurangi Kantong Belanja Plastik - Humairoh, Humairoh; Annas, Mohammad (Jurnal Manajemen, 2022)
The environmental damage because by plastic waste is very stressful. Indonesia is the second country in the world to supply plastic waste into the ocean after China. one of the prevention efforts is to reduce using plastic shopping bags originating from the modern retail industry. This examines goals to analyze the impact of green promotion, green e-wom, and green consumer satisfaction factors on interest in the usage of zero plastic shopping bags and consumer behavior in reducing plastic shopping bags. The sample in this examination had 98 respondents who shop at modern retailers within the Tangerang area, Banten Province in assembly their each-day desires. The sampling approach used was purposive sampling. statistics collection used a survey approach with a questionnaire that was distributed thru the G-shape electronically. The statistics are processed with the assistance of the smart-PLS software program. The results display the positive effect of green marketing, green e-wom, green satisfaction, and interest in the use of zero plastic shopping bags on consumer behavior to reduce plastic shopping bags, both in part or simultaneously.